(untitled) (Stamford Journal of Pharmaceutical Sciences, 2012)
The present study was undertaken to find out the promotional strategies followed by the pharmaceutical companies, attitudes and responses of physicians towards these promotional activities and influence of using gifts as promotional materials on the prescribing behavior of the physicians. In the study we found that most pharmaceutical companies believe that pharmaceuticals should be promoted by their quality and availability, not by any other promotional strategies. 84.62% pharmaceutical companies believe that gifts provided by them motivate the physicians to prescribe their products whereas 87% physicians admit that they consider the image of the company and quality of the product while prescribing. We also found that 50.5% physicians preferred information more rather than attractive gifts but only 11.77% pharmaceutical companies agreed with this statement. DOI: http://dx.doi.org/10.3329/sjps.v4i2.10434 S. J. Pharm. Sci. 4(2) 2011: 13-18